Islam, Ilmu-Ilmu Sosial, dan Masyarakat Sipil - Syed Farid Alatas (Antropologi Indonesia, 2001)
This paper provides an outline for the study of the role of the social sciences in the study of the workings of civil society in the context of Indonesian and Malaysian Islam. It begins with a discussion on the concepts of civil society and masyarakat madani, term often mistranslated and misunderstood as civil society. It is through a comparison of the two that the relevance of civil society in terms of its theory and practice to Islam is established. Next, I turn to a discussion of the types of use of the social sciences by the various components of civil society. This is followed by a discussion on the need for an account of the impact of the social sciences on public discourse, policy-makers, legislators and NGOs. To the extent that the social sciences do impact in the above arenas, how we may understand the relevance of Islam in this respect is addressed. I conclude by way of an exposition of the relationship between the concepts of civil society and masyarakat madani in the context of the need for a moral public.